STRATEGI KREDIT MACET “PANG PADE PAYU” PADA LEMBAGA PERKREDITAN DESA DI KABUPATEN BULELENG - Ni Made Sri Ayuni; Ni Wayan Novi Budiasni (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThis research is motivated by the phenomenon in the district of Buleleng related to the number of LPDs with unhealthy conditions until jammed have increased. In addition, the number of LPDs that have jammed in Buleleng Regency has the highest number in Bali. The purpose of this study is to know the implications of the internal control system and credit policy on credit settlement strategies, the disruption of bad credit is solved by the principle of